The EcoThermo Project: Key and Innovative Aspects. (November 2015) - Bari, F.; Mereu, D.; Damarco, C.; Greco, C.; Malan, S.; Marchetto, G.; Tirado, S. Roa; Tisseur, R.; Violante, M.; Zangari, G.; Caruso, S.; Masoero, M.; et al.
Abstract: In this paper we present the most innovative aspects of the EC-FP7 EcoThermo project. The main aim of the project consists on innovating the technique of heat cost allocation in buildings with a centralized heating system, overcoming the heat cost allocator drawbacks for reliability, measurement reproducibility and traceability and contexts of applications. Given the complexity of the project, we will focus on its main aspects, such as the use of a virtual sensor to estimate the radiators heating power, the design of electronic valves fitted out with an energy harvesting system and the original wireless communication protocol.